WORLDVIEW AND MEMORY IN THE NOVELS OF ALTERNATIVE HISTORY META-GENRE AS AN EXPRESSION OF “INTERNAL EMIGRATION” - Antonina V. Anistratenko (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2019)
The article deals with the worldview and memories in the alternative history novels meta-genre, its stylistic, genre markers and common plot characteristics, which realize the concept of the “insight emigration”. Alternate history meta-genre is presented here as the basic genre formation which derivate own subgenres with similar and different markers, that all works as a basis of the “insight emigration” concept. The text research is based on the novels of V. Tarnavsky “Empty Pedestal”, V. Aksyonov “Island of Crimea”, D. Odiya “Tartak”, V. Kozhelyanko “Children of the stagnation” and Pierre DBC “Light out in Wonaerland”. The article’s goal is to determine the identify the way of the special complex of genre and stylistic markers forming the concept of “insight emigration”of alternative history meta-genre novels and this finding means article’s novelty. In the novel “Tartak” D. Odiya describes the “Post-Pegeerian” Poland in its category B, as indicative marker of the novel’s space. In the novel we see the pessimistic mode of the ashes, in which the characters are mostly unemployed and homeless, alcoholics, drug addicts, small criminals and cheap prostitutes. Outsiders and marginalized generations are lost in time and space between a joyous past and a hopeless future. Their migration takes place without any prefixes, since it has no direction of movement, because these people do not have a place to go to in the outside world (where nobody expects them), nor in the inner world (which is devoid of memory – the last travel guide). In contrast to “Tartak” the poetics of the novel “Children of Stagnation” by V. Tarnavskiy is inextricably linked with the facts of the USSR’s finish and the already mentioned “repressive discourse”, which remained as a trail of history in history. In the performance of Pierre DBC, in the novel “Lights out in Wonderlan” we can see depressive urban space, even similar to the the fiction world of Russian writer E. Zamyatin, who wrote novel “We” about the communist world with his repressive discourse with only single escape – the “internal emigration”. The author catches into field of sarcasm the real Soviet reality. And Peter Warren Finley (the real name of Pierre DBC), and the Soviet citizen of Russia E. Zamyatin, in fact intend in the novels blaming position to the British Empire and the “Empire of Evil”. Methods of research. For analyzing is used descriptive method, comparative method and analytical principle. The cultural method is also used to indicate the cultural status of the antinomy “memory‑forgetting”, determine its range of control in the plot of fiction literature works and compare the result to different national literature on the basis of some novels. The novelty of the article is that, it is realized for the first time the comparison of “internal emigration” in West-European, Slavic literatures and Russian literature as the concept of post-colonial studies. Textually the research is based on the five novels. Conclusions. Consequently, worldview and memory are often embodied in intellectual characters (sometimes marginal status) and as expressions of the internal emigration of an intellectual person who in today’s consumer society finds no place in either the homeland or emigration in the works of alternative history meta-genre. The “internal emigration” in the literature of the alternative history appears to be a specific mechanism for implementing the antinomy of “memory-forgetting” on the side of forgetting in the Western Slavic literature and literature of the Slavic world (Polish, Ukrainian, and Czech) and on the side of memory in Russian literature. The divergence of this discourse vector is related to the functioning of artistic systems in postcolonial and anti-colonial spaces.